A comparison of sodium silicate and ammonium lignosulfonate effects on xenotime and selected gangue mineral microflotation. (January 2017) - Zhang, Yicheng; Anderson, Corby
Highlights: The fundamentals of xenotime flotation have been researched. The use of sodium oleate and octano-hydroxamic acid collectors has been researched and compared. The fundamentals of the flotation depression of four common gangue minerals have been researched. The use of sodium silicate and ammonium lignosulfonate depressants has been researched and compared. Abstract: Because of their selective depressing power, sodium silicate and lignosulfonate have been widely used as depressants in rare-earth mineral flotation to separate minerals from specific types of gangue minerals. In this project, the microflotation of a xenotime pre-concentrate and pure samples of the selected gangue minerals ilmenite, zircon, schorl and staurolite was carried out. This utilized octano-hydroxamic acid and sodium oleate as the collectors and the research was conducted in a Partridge-Smith microflotation cell. The flotation of the mixed samples (weight ratio = 1:1) of xenotime and each one of its gangue minerals was also investigated at both room temperature and 80 °C, using sodium silicate or ammonium lignosulfonate in the presence of octano-hydroxamic acid and sodium oleate respectively. The flotation results are described and compared with those observed by previous researchers. The effects of sodium silicate and ammonium lignosulfonate on weight recoveries and grade of xenotime are also discussed and compared.